Acute Effects of Dry Needling on Lower Limb Muscle Strength in CrossFit Athletes with Latent Trigger Points: A Randomized Triple-Blinded Pilot Clinical Trial - Andres Rojas-Jaramillo; Daniel Quintero-Lotero; Camilo Garcia-Torres; Jorge L. Petro; Diego A. Bonilla (OVS LLC, 2023)
Study purpose. The purpose of this study was to evaluate the acute effect of deep dry needling (DP) on lower-limb muscle strength-related variables in CrossTraining recreational athletes with latent trigger point (TrP). Materials and methods. A total of 19 healthy CrossFit®-trained males (27.8 [4.7] years; 79.8 [10.4] kg; 1.76 [0.07] cm) with myofascial TrP in quadriceps, gluteus or gastrocnemius muscles completed this repeated-measures triple-blind pilot clinical trial. Participants were randomly allocated into either experimental (EG, n = 10) or Sham (SG, n = 9) groups. After allocation, the assessment of lower-limb muscle power (squat jump [SJ] and countermovement jump [CMJ]) and maximal isometric hip abduction and quadriceps strength were measured at baseline and after 48 hours of the intervention. Results. The results are expressed as Δ (SD) [95% CI]; unbiased Cohen's d [dunb, 95% CI]). DN has been shown to reduce the presence of muscle TrP. The maximal isometric hip abduction strength had a moderate-to-high significant increase in the EG (left: 21.5 (16.9) [9.42, 33.57]; 0.55 [0.19, 0.99], right: 20.3 (16.2) [8.70, 31.89]; 0.74 [0.25, 1.35]); however, the Sham group only showed significant improvement in the left hip abductor muscles 15.77 (15.37) [3.96, 27.59]; 0.57 [0.11, 1.12]) with no significant changes in the right side. Conclusions. The acute reduction of myofascial TrP was observed with the application of DN but had no significant effect on maximal isometric strength or jump height compared to the Sham group. Results of this pilot clinical trial can be used to commission future research.